Are neighbors equal?: Estimating local inequality in three developing countries - Elbers, Chris; Lanjouw, Peter; Mistiaen, Johan; Özler, Berk; Simler, Kenneth R. (International Food Policy Research Institute, 2003)
A methodology to produce disaggregated estimates of inequality is implemented in three developing countries: Ecuador, Madagascar, and Mozambique. These inequality estimates are decomposed into progressively more disaggregated spatial units and the results in all three countries are suggestive that even at a very high level of spatial disaggregation, the contribution of within-community inequality to overall inequality remains very high. The results also indicate there is a considerable amount of variation across communities in all three countries. The basic correlates of local-level inequality are explored, and it is consistently found that geographic characteristics are strongly correlated with inequality, even after controlling for demographic and economic conditions."" -- Authors' Abstract